THE CORRELATION BETWEEN SOCIAL MEDIA ACTIVENESS AND VOCABULARY MASTERY OF THE ENGLISH DEPARTMENT STUDENTS OF UNIVERSITAS RIAU - Ovia Nabilla; Rumiri Aruan; Novitri Novitri (International Journal of Educational Best Practices, 2022)
The aim of this research is to discover the correlation between social media activeness and vocabulary mastery of the English department students of Universitas Riau. The population of the research is all third-year students of the English department of Universitas Riau. The number of samples is 117 students. The research instruments are 1) a questionnaire, and 2) a test. The questionnaire is for the data on social media activeness while the test is for the data on vocabulary mastery. To analyze the data, the researchers employed IBM SPSS Statistics 25. The data analysis revealed that the mean score of the student’s social media activeness is 20.2, classified as 'high' level, whereas the mean score of the student’s vocabulary mastery is 69.3, categorized as 'good' level. Additionally, the research finding showed the correlation coefficient of the two variables is 0.480, denoting a positive and moderate correlation. Also, the determinant coefficient is 0.2304, which implies social media activeness has a 23% influence on the students' vocabulary mastery, leaving the other 77% to other factors. Having discovered that there is a moderately significant correlation between social media activeness and vocabulary mastery, it is suggested that the students need to start utilizing their social media well and wisely. Besides providing entertainment, social media can be a great platform for students to improve their English vocabulary mastery.